Learning history in America : schools, cultures, and politics - Kramer, Lloyd S.; Reid, Donald; Barney, William L. (University of Minnesota Press, 1994)
As it extends recent discussions about multiculturalism into the sphere of contemporary historical understanding, this book sets out explicitly to explore the practical and theoretical implications of these discussions for people who learn and teach history in the United States.